Prospects for The Development of the EAEU Integration Processes in The Context of Energy Security - Natalya Yu. SOPILKO; Natalia A. NAVROTSKAIA; Natalya V. BONDARCHUK (Communications of International Proceedings, 2021)
The article discusses the evolution of the energy security concept for countries, describes the approaches of Western European and Asian specialists to its essence, and also presents the approach of Russian researchers. The relevance of energy security issues for the countries of the Eurasian Economic Union (EAEU) has been determined. The promising areas for strengthen energy security in the Eurasian region have been considered. The expediency of the formation of a Common Energy Space on the Eurasian continent with the participation of countries neighboring the EAEU has been substantiated. It has been suggested that the development of the Energy Ring project in Eurasia will become the new general trend of the world energy sector and will form a new dimension of the fuel and energy complex (FEC) in the context of ensuring the collective energy security of countries.
Keywords: Energy Security; EAEU; Energy Integration; Energy Ring.